Правове регулювання добровільної відмови від спеціального природокористування - Кирєєва, І. В.; Kyrieieva, I. V.; ORCID: http://orcid.org/0000-0001-5447-4314 (Юридичний науковий електронний журнал. - 2019. - № 1. - С. 110-113, 2019)
Стаття присвячена дослідженню порядку правового регулювання добровільної відмови від спеціального природокористування. Проаналізовано норми природоресурсного законодавства, що регулюють добровільну відмову від права спеціального природокористування, зокрема щодо припинення відносин спеціального водокористування та надрокористування. Акцентовано увагу на тому, що необхідною умовою припинення права спеціального природокористування внаслідок волевиявлення природокористувача є додержання встановленого порядку такого волевиявлення. З’ясовано, що в основі добровільної відмови від права спеціального природокористування мають бути принципи добровільності волевиявлення, належного правового оформлення відмови від спеціального природокористування, прийняття рішення про припинення права спеціального природокористування компетентним суб’єктом, як правило, органом, який надав дозвіл на спеціальне природокористування, належний стан природних об’єктів, що повертаються до власника або уповноваженого ним суб’єкта, такі природні об’єкти мають бути придатні для подальшого їх використання за відповідним цільовим призначенням. У результаті дослідження запропонована деталізація правового регулювання порядку припинення права спеціального природокористування на рівні підзаконного нормативно-правового акта.

The article is focused on the research of the procedure of legal regulation of voluntary abandonment from special exploitation of natural resources. The author has analyzed the norms of the natural resources law regulating the voluntary abandonment from the right to special exploitation of natural resources, in particular, regarding the termination of relations of special water use and subsoil use. It has been established that the lack of unity among regulatory acts regarding the formulation of the grounds, which reflect the initiative of natural resource users, aimed at terminating the right of special use of any natural object is the characteristic for the current state of legal regulation of the termination of the right of special exploitation of natural resources. Special emphasis has been paid to the fact that the necessary condition for the termination of the right of special exploitation of natural resources as a result of the expression of will of natural resources users is the observance of the established procedure of such an expression of will. On the basis of the analysis of the natural resource law, it has been concluded that the existence of a written statement by a natural resources user as a precondition for making a decision to terminate the right of special exploitation of natural resources and consolidating the need to submit such an application may serve as a mean of protecting the rights and legitimate interests of a natural resources user, preventing their violation. However, the acceptance of the application for a voluntary abandonment from the right to use natural resources may not be identical to its satisfaction. The author has established that the basis of voluntary abandonment from the right to special exploitation of natural resources should be the principles of voluntary expression of will, proper legalization of the abandonment from special exploitation of natural resources, taking the decision to terminate the right of special exploitation of natural resources by a competent entity, as a rule, by the authority that granted the permission for special exploitation of natural resources, proper state of natural objects that are returned to the owner or an agent authorized by him, such natural objects must be suitable for their further use for the intended function. As a result of the study, the author has offered the implementation of the said principles by providing details of legal regulation of the procedure for termination of the right of special exploitation of natural resources at the level of the by-law regulatory act. The author of the research offers, among other things, to set a certain period, within which the owner or the authorized by him agency will be able to verify the submitted application for voluntary abandonment of special exploitation of natural resources and related accompanying documents, as well as to conduct a direct review and verification ofthe state ofthe natural object being in use.

Статья посвящена исследованию порядка правового регулирования добровольного отказа от специального природопользования. Проанализированы нормы природоресурсного законодательства, регулирующего добровольный отказ от права специального природопользования, в частности относительно прекращения отношений специального водопользования и недропользования. Акцентировано внимание на том, что необходимым условием прекращения права специального природопользования в результате волеизъявления природопользователя является соблюдение установленного порядка такого волеизъявления. Установлено, что в основе добровольного отказа от права специального природопользования должны быть положены принципы добровольности волеизъявления, надлежащего правового оформления отказа от специального природопользования, принятия решения о прекращении права специального природопользования компетентным субъектом, как правило, органом, который предоставил разрешение на специальное природопользование, надлежащее состояние природных объектов, возвращаемых владельцу или уполномоченному им субъекта, такие природные объекты должны быть пригодны для последующего их использования за соответствующим целевым назначением. В результате исследования предложена детализация правовой регуляции порядка прекращения права специального природопользования на уровне подзаконного нормативно-правового акта.
Legal regulation of voluntary abandonment from special exploitation of natural resources
Кирєєва І. В. Правове регулювання добровільної відмови від спеціального природокористування [Електронний ресурс] / Кирєєва І. В. // Юридичний науковий електронний журнал. - 2019. - № 1. - С. 110-113. - Режим доступу: http://www.lsej.org.ua/1_2019/30.pdf.
Keywords: Земельне право. Аграрне право. Land Law. Agrarian Law. Земельное право. Аграрное право; Екологічне право. Environmental law. Экологическое право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; природокористування; спеціальне природокористування; припинення права природокористування; добровільна відмова від природокористування; exploitation of natural resources; special exploitation of natural resources; termination of the right to exploit natural resources; voluntary abandonment from the exploitation of natural resources; природопользование; специальное природопользование; прекращение права природопользования; добровольный отказ от природопользования